2007
DOI: 10.1088/0953-8984/19/17/176203
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of optical and magneto-optical properties of GdFe2and GdCo2

Abstract: We report calculations of the optical and magneto-optical properties of GdFe(2) and GdCo(2) using the full-potential linear-augmented-plane-wave method. Calculations with the Coulomb corrected local spin density approximation (LSDA+U) give a better representation of the band structure, density of states and magnetic moments compared to LSDA alone. However, both LSDA and LSDA+U approximations give fairly good agreement with experiment for the diagonal optical conductivity. The calculated results for GdCo(2) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
2
9
0
4
Order By: Relevance
“…These peaks consist of the Gd (4f) state. For minority spins, this state is hybridized with d and p bands of Co, while it is unhybridized in the case of majority spins [6].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks consist of the Gd (4f) state. For minority spins, this state is hybridized with d and p bands of Co, while it is unhybridized in the case of majority spins [6].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…For many years, researchers have been studying rare earth/transition metal (RE/TM) compounds, including the electronic properties of GdFe 2 , GdCo 2 , (Y,Gd)Co 2 , YCo 2 , La 2 Co 7 [6][7][8][9], and the magneto-optical properties of different RE/TM compounds like GdFe 2 , HoFe 2 , ErFe 2, TbFe 2 , DyFe 2 and YFe 2 [10,11]. A magnetocaloric effect was studied in GdCo 5 alloys which exhibit magnetic phase transition near the room temperature [12].…”
Section: Introductionmentioning
confidence: 99%
“…The value of the Hubbard potential for dysprosium is based upon the literature [31] with U=0.49 Ryd and J=0.05 Ryd. Coulomb-corrected local spin density approximation (LSDA + U) was applied, as this method, introduced by Anisimov, et al [32], is found to be very efficient for several rare-earth compounds [33,34,35,36,37,38,39].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Though we performed spin polarised calculations for various exchange correlation schemes, viz., Local Spin Density Approximation (LSDA), PBE and (LSDA + U) on DyPdBi, the DoS histograms are analyzed for LSDA and (LSDA + U) [12,33,34,35,36,37,38,39] alone as these methods are known to be rather efficient for many of the rare-earth compounds. , drawn for spin-down states, it can be inferred that the total DoS at the Fermi energy level is almost all due to dysprosium and has increased from 26 states/eV to 30 states/eV.…”
Section: Density Of States (Dos)mentioning
confidence: 99%
“…Для интерметаллидов GdFe 2 и LuFe 2 рядом авторов были выполнены вычисления электронной структуры [12][13][14][15][16][17][18][19], показавшие, что вблизи уровня Ферми происходит сильная гибридизация широких 3d-зон железа и 5d-зон редкоземельного металла, тогда как 4 f -зоны Gd и Lu локализованы в узких областях энергий. На основе таких расчетов были интерпретированы результаты по исследованию фотоэмиссии и поглощения рент-геновского излучения [20][21][22].…”
Section: Introductionunclassified